Do players with superior physiological attributes outwork their less-conditioned counterparts? A study in Gaelic football - Lorcan S. Daly; Ciarán Ó. Catháin; David T. Kelly (Termedia Publishing House, 2023)
This study investigated the association of physiological attributes with in-game workload measures during competitive Gaelic football match-play. Fifty-two male developmental level Gaelic football players (mean ± SD; age: 22.9 ± 3.8 years) underwent measurements of anthropometric characteristics, running speed, muscular strength and power, blood lactate (BLa), running economy and aerobic capacity during two separate testing visits. Global Positioning System units (18-Hz) were used to record players in-game workloads during a competitive match 1-week following the baseline physiological assessments. Results indicated that players body fat percentage, drop jump height (DJ) and running velocity at 4 mmol · L −1 BLa were significantly associated with the number of high-speed runs completed (Adjusted R 2 26.8% to 39.5%; p < 0.05) while 20 m running speed, running velocity at 2 mmol · L −1 BLa and DJ were significantly associated with the number of accelerations completed (Adjusted R 2 17.2% to 22.0%; p < 0.05) during match-play. Additionally, aerobic capacity and body fat percentage were significantly associated with total distance (Adjusted R 2 14.4% to 22.4%; p < 0.05) while body fat percentage, DJ and 20 m running speed were significantly associated with high speed distance (Adjusted R 2 17.8% to 22.0%; p < 0.05). Players were also divided into higher-standard and lower standard groups using a median split of these physiological attributes. Players in the higher-standard groups completed significantly more high-speed runs and accelerations and covered significantly larger total and high-speed distances (+10.4% to +36.8%; ES = 0.67 to 0.88; p < 0.05) when compared to the lower-standard groups. Thisstudy demonstrates that superior levels of physical conditioning are associated with larger in-game workloads during Gaelic football match-play.